Facial Scar Improvement Procedures - Newberry, Christopher Ian; Thomas, J. Regan; Cerrati, Eric W. (Facial Plastic Surgery, 2018)
Scars are a natural part of dermal healing following lacerations, incisions, or tissue loss. The ideal scar is narrow, flat, level with surrounding tissue, and difficult for the untrained eye to see due to color match and placement parallel to relaxed skin tension lines; however, scarring that is dyspigmented, hypertrophied, widened, contracted, or atrophic can be aesthetically displeasing or causing functional limitations. When the scar has unfavorable characteristics, scar revision is often indicated and the cosmetic surgeon must be knowledgeable of the minimally invasive as well as surgical techniques to improve aesthetics, reduced reoccurrence, or correct functional limitations.
Keywords: scar revision; dermabrasion; laser resurfacing; z-plasty; scar camouflage